Application of automated nonparametric statistical analysis in clinical contexts. Issue 2 (20th October 2020) - Kranak, Michael P.; Falligant, John Michael; Hausman, Nicole L.
Abstract : Functional analyses (FAs) provide clinicians with results upon which they design behavioral treatments. Unfortunately, interrater reliability of visual analysis of FA results can be inconsistent. Accordingly, researchers have designed quantitative metrics and visual aids to supplement visual analysis. Recently, Hall et al. (2020) provided a proof of concept for using automated nonparametric statistical analysis (ANSA) to interpret FA data. Their results show promise for ANSA as a supplemental tool. However, they evaluated ANSA with only published FA datasets, which may not be representative of FAs commonly encountered in clinical care. Therefore, the purpose of this replication was to compare ANSA to another validated supplemental aid (i.e., the structured criteria method) and investigate its utility with unpublished clinical FA data. Our results were consistent with Hall et al.'s, indicating ANSA may augment clinical interpretation of FA data. Recommendations for clinical applications of ANSA and future directions for researchers are discussed.